The Effectiveness of The Indonesian Language Intensive Program For Foreign Students at UIN Imam Bonjol Padang - Reza Fahmi; Prima Aswirna (Bersama : Jurnal Pengabdian Masyarakat, 2026)
This study examines the effectiveness of an intensive Indonesian language program for international students at UIN Imam Bonjol Padang. The program aims to enhance communicative competence, academic literacy, and intercultural adaptation among foreign learners enrolled in various study programs. Using a quasi-experimental design with pre-test and post-test measures, this study involved 32 international students participating in a 12-week intensive Bahasa Indonesia bagi Penutur Asing (BIPA) program. Data were collected through language proficiency tests, self-efficacy questionnaires, and classroom observations. The findings indicate a significant improvement in students’ listening, speaking, reading, and writing skills after program completion. Additionally, students reported higher academic confidence and improved sociocultural adjustment. The results suggest that structured intensive instruction combined with contextual and intercultural approaches effectively supports foreign students’ linguistic and academic integration. The study recommends strengthening curriculum design, digital learning integration, and continuous evaluation to sustain program quality.